Regional consequences of the economic and social transformation: Case study Slovakia - Milan Bucek; Jozef Busik (European Regional Science Association (ERSA), 1998)
Regional situation in time of changes, just before the beginning of the transformation process: * regional monostructure and " district industrialisation", flagships and big enterprises, * full regional employment , but rather low competitiveness, * structural problems (the structure of sectors, low share of the service activities, huge concentration of arm industry in the selected regions etc.), * regional consequences of the eastern trade orientation. The process of global economic and regional transformation: * the radical economic reform, the regional differentiation process of the production's declining and unemployment, * the disintegration of large enterprises , a new western trade reorientation, * the investment's declining But in the same time the beginning of positive trends: the massive development of the private sector, explosion of SME * a steady growing share of service activities connected with foreign direct investments (banks, financial institutions, hotel chains, consulting, audit and marketing agencies etc. ) Generally: a very different reaction of the regions on this development and the adaptability on the transformation process. An active regional policy at the beginning: * the regional development programs * the new regional institutions * the governmental support for the depressed regions * EU support ( cross-border co-operation, the regional development agency and investment fund) The core region of the capital Bratislava and Slovak periphery. Challenges and risks of Bratislava-Vienna region. Spatial consequences on the location of economic activities.
Keywords: 330